Taslima Nasreen: looking at Nasreen’s exploration of female sexuality, Nasreen as a feminist in the context of Bangladeshi women’s movement and Nasreen as a woman poet - Nitol, Afsana Aziz (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.